Thermoelectric Generator Performance as a Power Generator in a Portable Stove - Jayanegara, Sudarmanto (Journal of Science and Engineering, 2025)
A thermoelectric generator (TEG) is a device that can convert heat energy into electrical energy through the Seebeck effect. This study aims to analyze the performance of a TEG as a power generator in a portable stove by utilizing the waste heat generated during the combustion process. Tests were conducted with varying temperature differences between the hot and cold sides of the TEG, as well as measuring the output power and energy conversion efficiency. The results show that the performance of a TEG is greatly influenced by the given temperature difference, where increasing the temperature on the hot side and optimal cooling on the cold side can increase the electrical power generated. Although the conversion efficiency is still relatively low, this system has potential as an alternative power source for small devices in off-grid environments. This study is expected to be a reference in the development of thermoelectric technology for portable and renewable energy applications.